Traditional Justice System as Alternative Dispute Resolution Under Article 159(2)(C) of the Constitution of Kenya, 2010 - Kinama, Emily (Strathmore Law Journal, 2021)
There are various forms of justice. It cannot be limited to legal justice. This paper explores the potential of traditional justice systems under the Constitution. It illustrates the need for a multidisciplinary approach in order to fully realise the right to access justice. Through a comparative analysis as well as case law, the paper demonstrates how alternative dispute resolution is not limited to civil cases, but can be applied to criminal proceedings. Challenges are pointed out and recommendations made on how to improve and effectively manage traditional justice system